A Therapeutic Journey of 5-Pyrazolones as a Versatile Scaffold: A Review - Sharma, Ravinder; Chawla, Pooja A.; Chawla, Viney; Verma, Rajeev; Nawal, Nandita; Gupta, Vikas (Mini Reviews in Medicinal Chemistry, 2021)
A sizeable proportion of currently marketed drugs come from heterocycles. The heterocyclic moiety 5-pyrazolone is well known five-membered ring containing nitrogen. Derivatives of this wonder nucleus have exhibited activities as diverse as antimicrobial, anti-inflammatory, analgesic, antidepressant, anticonvulsant, antidiabetic, antihyperlipidemic, antiviral, antitubercular, antioxidant, anticancer and antiviral, including action against severe acute respiratory syndrome (SARS) or 3C protease inhibitor. A number of drugs based on this motif have already made it to the market. Standard texts and literature on medicinal chemistry cite different approaches for the synthesis of 5- pyrazolones. The present review provides an insight view to 5-pyrazolone synthesis, their biological profile and structure-activity relationship studies.
Keywords: antidiabetic